Standard or accelerated methotrexate, vinblastine, doxorubicin and cisplatin as neoadjuvant chemotherapy for locally advanced urothelial bladder cancer: Does dose intensity matter?. (February 2016) - Pouessel, Damien; Chevret, Sylvie; Rolland, Frédéric; Gravis, Gwenaelle; Geoffrois, Lionel; Roubaud, Guilhem; Terrisse, Safae; Boyle, Helen; Chevreau, Christine; Dauba, Jérôme; Moriceau, Guillaume; Alexandre, Ingrid; et al.
Abstract: Background: There is continuing controversy regarding the optimal regimen for neoadjuvant chemotherapy (NAC) in bladder cancer. Patients and methods: We performed a retrospective analysis of 241 consecutive bladder cancer patients who received a combination of methotrexate, vinblastine, doxorubicin and cisplatin (MVAC) using a standard (52 patients) or an accelerated schedule (189 patients) as NAC before radical cystectomy in 17 centres of the French GEnito-urinary TUmour Group from March 2004–May 2013. Results: The median age was 62 years. As expected, the median number of cycles, the median total dose of cisplatin and the median cisplatin dose intensity were higher in patients treated with the accelerated regimen. Conversely, the median duration of chemotherapy was shorter. Regarding toxicity, grade III/IV neutropenia, grade III thrombocytopenia and grade III anaemia as well were more frequently observed in patients treated with the standard regimen. Among 211 (88%) patients who proceeded to cystectomy, 75 (35%) patients achieved an ypT0 pN0 status (no pathologic residual tumour cells) with no significant difference according to the MVAC schedule. Three-year overall survival rates were 66.5% (95% confidence interval [CI], 56–79) and 72% (95% CI, 59.5–88) in the standard and accelerated cohorts, respectively. In the multivariate analysis, two independent prognostic parameters were retained: the ypT0 stage and the ypN0 stage. Heterogeneity test did not show any interaction with NAC regimens. Conclusion: Similar pathological response and survival rates were observed whatever the chemotherapy regimen used. Haematological toxicity was greater in patients who received standard MVAC. Highlights: There is level 1 evidence for neoadjuvant chemotherapy in bladder cancer. Two different schedules of chemotherapy were retrospectively assessed. Outcomes in terms of efficacy and toxicity favoured the accelerated regimen.